Provision of Abortion Caused by Rape and Adultery in Islam | حكم الإجهاض الناتج من الزنا والاغتصاب في ميزان الإسلام - Rusli Hasbi (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
This article discusses about law of abortion according to Muslim jurisprudenceviews. Types of law of abortion related to the causes and age of embryo isdiscussed. There is an abortion in order to protect a mother’s soul, and there isan abortion because of adultery or rape. Related to age of embryo, there is anabortion done before or after fourth of month of embryo age. Based on thosedifferent causes and reasons, the outcome of law of abortion is also different.The research explains the definition of abortion referred to the Arabicdictionaries. Besides that, the writer also explores diversification of Muslimjurisprudence, such as classic and modern views. Lastly, the writer affirms oneof those Muslim jurisprudence views as well as he offers his own view.